In Vitro and in Vivo Anthelmintic Activities of Aqueous Leaf Infusion of Azadirachta indica against Haemonchus contortus - A. A. Sakti; Kustantinah Kustantinah; R. W. Nurcahyo (Faculty of Animal Science, Bogor Agricultural University, 2018)
Anthelmintic resistance of Haemonchus contortus worm has become a major problem in ruminant production. Traditional medicinal and potential tropical plants with high tannin contents have a great potency as an alternative source of bio-anthelmintic. The study was carried out to assess the in vitro egg hatches inhibiting (EHI) and adult worm motility (AWM) tests and in vivo anthelmintic activities of aqueous leaf infusion of Azadirachta indica against H. contortus. Leaf infusion at doses of 2%, 4%, and 6% were used for in vitro treatments, and albendazole at a dose of 2 mg/mL was used as a positive control and 0.9% of sodium chloride was used as a negative control. The EHI assay was conducted two times i.e., before treatment and 24 h after treatment. The AWM were monitored 15 and 30 min, and 1, 2, 3, 4, 5, 6, 7, and 8 h post treatment. Sixteen Javanese Thin Tail ewes at the ages of ±12 months that naturally positive of H. contortus with about 1.000 EPG were selected and allocated randomly to 4 groups (n= 4). They were subsequently received the ensuing treatments i.e., A. indica infusion at doses of 0% (A) as a control, 6% (B), 8% (C), and 5 mg/BW albendazole (D) at a single oral dose as a positive control. Experimental ewes in Groups B and C were given oral infusion weekly during 4 weeks of treatment. EPG’s fecal examinations were conducted weekly. The result showed that the leaf infusion of A. indica containing condensed tannin (CT) at a dose of 6% significantly inhibited egg hatching (P<0.05) with a better effect compared to doses of 0%, 2%, and 4%. In AWM test, three doses of infusion significantly difference each other, as well as both negative and positive controls (P<0.05). After treatment, both of the A. indica containing CT levels and albendazole reduced EPG count significantly (P<0.05). Meanwhile, significant difference was not detected in dose of 8% aqueous leaf infusion of A. indica and albendazole treatments on weeks 3, 4, 5, and 6 consecutively. In conclusion, the aqueous leaf infusion of A. indica is fully potential as a bio anthelmintic against H. contortus.